Norma sebagai Sarana Menilai Bekerjanya Hukum dalam Masyarakat - Budi Pramono (Faculty of Law Hang Tuah University, 2017)
In this life people need to socialize and have some interaction, and for controlling the interaction they need norm, such as religion norm, obscenity, decency and law norm. Norm can be used to become a tool for evaluating how the law works in community, like the law making processes, the law implementing processes and the role occupant.